Case Report: A Boy From a Consanguineous Family Diagnosed With Congenital Muscular Dystrophy Caused by Integrin Alpha 7 (ITGA7) Mutation - Xia, Wenqing; Ni, Zhumei; Zhang, Zheng; Sang, Hongfei; Liu, Huifang; Chen, Zhenzhen; Jiang, Lin; Yin, Congguo; Huang, Jinyu; Li, Lingfei; Lei, Xiaoguang (Frontiers in Genetics, 2021)
Introduction: Congenital muscular dystrophy (CMD) is a group of early-onset disorders with clinical and genetic heterogeneity. Patients always present with muscle weakness typically from birth to early infancy, delay or arrest of gross motor development, and joint and/or spinal rigidity. There are various genes related to the development of CMD. Among them, mutations in integrin alpha 7 (ITGA7) is a rare subtype. The identification of disease-causing genes facilitates the diagnosis and treatment of CMD. Methods: We screened ITGA7 mutations in four people by whole exome sequencing and targeted sequencing from a consanguineous family. We then carried out electromyography and neuroelectrophysiological examinations to clarify a clinical picture of the patient diagnosed with CMD. Results: We report a Chinese boy diagnosed with CMD who carries a homozygous variant (c.1088dupG, p.H364Sfs*15) of the ITGA7 gene. According to the genotype analysis of his family members, this is an autosomal recessive inheritance. Conclusions: Our case further shows that ITGA7 mutation is related to CMD. Genetic counseling and multidisciplinary management of CMD play an important role in helping patients and their family. Further elucidation of the significant clinical and genetic heterogeneity, therapeutic targets, and the clinical care for patients remains our challenge for the future.